KARAKTER LANSKAP BUDAYA RUMAH LARIK DI KOTA SUNGAI PENUH, PROVINSI JAMBI - Hasibuan, M. Sanjiva Refi; Nurhayati, .; Kaswanto, Regan Leonardus (Jurnal Lanskap Indonesia, 2017)
Rumah larik cultural landscape is the traditional settlement landscape of Kerincinese. The landscape reflects the history and cultures of kerincinese which still survive today. But nowadays, the characters of this cultural landscape increasingly degraded by urbanization. There are three rumah larik cultural landscape that still exist in Sungai Penuh City, Rumah Larik Enam Luhah, Rumah Larik Pondok Tinggi, and Rumah Larik Dusun Baru. The aim of this study is to identify the characters of rumah larik cultural landscape. Data and information were collected by desk study, field survey, and depth interview. Landscape Character Assessment (LCA) method used to analyze and assess the character of rumah larik cultural landscape. The result of this study are rumah larik cultural landscape characters is agricultural and local natural resource based. The character area is rumah larik settlement area with long-parallel cluster pattern and close by water resource. The key characteristics are the elements of landscape such as rumah larik, mosque, surau, bilik padi, tabuh larangan, ancestral burial grounds, and rivers.